Exploring Number Concept Mastery: A RASCH Analysis of Flipped Classroom Learning for Future Elementary Teachers - Irni Rachmawati Putri; Rahayu Condro Murti; Fery Muhamad Firdaus (AL-ISHLAH: Jurnal Pendidikan, 2025)
Mastering the concept of numbers is a critical competency for prospective elementary school teachers, as it forms the foundation of early mathematics instruction. This study explores the effectiveness of the flipped classroom model in enhancing number concept understanding, supported by RASCH analysis to measure and interpret student performance. A quantitative descriptive design was employed involving 39 first-semester students from Class D of the Elementary Teacher Education (PGSD) Program at Yogyakarta State University (Class of 2024). Data were collected using a multiple-choice test on number concepts, covering topics such as types of numbers, arithmetic operations, and number properties. The results were analyzed using the RASCH Model through WINSTEPS software, focusing on Wright Map, item fit, student ability, scalogram analysis, and test reliability. The RASCH analysis revealed that the flipped classroom model supported diverse levels of student understanding. The Wright Map indicated varied ability levels across students, while item fit statistics confirmed that most items functioned as expected. Scalogram analysis identified response patterns indicating careless mistakes, lucky guessing, and potential cheating. The test demonstrated high reliability in distinguishing between ability levels. Findings suggest that the flipped classroom model contributes positively to the conceptual understanding of number concepts, though learning gaps remain. The RASCH Model provided in-depth diagnostic insights, allowing for more targeted instructional improvements. The integration of flipped learning with RASCH-based assessment offers a robust framework for improving and evaluating mathematics instruction among prospective teachers.